Protection from cyclophosphamide-induced ovarian damage with bone marrow-derived mesenchymal stem cells during puberty. (February 2014) - Kilic, Sevtap; Pinarli, Ferda; Ozogul, Candan; Tasdemir, Nicel; Naz Sarac, Gulce; Delibasi, Tuncay
Abstract Objective: In female cancer survivors, the accelerated loss of primordial follicles may lead to premature ovarian failure. We investigated the protective effects of bone marrow derived mesenchymal stem cells (BMMSC) and gonadotropin releasing hormone analogue (GnRHa) against chemotherapeutic-induced ovarian toxicity in a rat model. Material and methods: Forty-eight Wistar albino female rats were divided into four groups. Group 1 was composed of rats that were given 200 mg/kg cyclophosphamide injection for each cycle (two cycles for each rat). Both cyclophosphamide and 0.4 µg GnRHa were administered to Group 2. Cyclophosphamide and 4 million/kg BMMSC were administered to Group 3. Cyclophosphamide, GnRHa, and BMMSC were administered to Group 4. Germ cell apoptosis, DNA fragmentation and primordial follicular count were investigated with Cleave Caspase-9 and TUNEL analysis. The presence of the SRY gene on the Y chromosome in the ovary of the recipient female rats was checked with PCR. Results: Immunohistochemical staining (IHS) of Caspase-9 and TUNEL was higher in Group 1 than in Group 3 (p < 0.05). Similarly, Group 4 had higher values than Group 3 (p < 0.05). The presence of the SRY gene was detected in Groups 3 and 4 with the PCR analysis. The mean primordal follicle count was lowest in Group 1 and the mean primordial follicle counts were higher in Groups 2 and 3 than in Group 1. The difference between Group 1 and Group 4 was not significant. Conclusion: BMMSC therapy was found to be protective from germ cell apoptosis and DNA damage when it was used with chemotherapy regimens including alkylating agents.